2014
DOI: 10.1111/den.12345
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic balloon dilatation for pharyngo‐upper esophageal stricture after treatment of head and neck cancer

Abstract: This retrospective analysis demonstrated the efficacy and safety of exclusive EBD for pharyngo-upper esophageal strictures occurring after treatment for head and neck cancer, indicating that the therapeutic application of EBD could be extended to such strictures. Patients who underwent chemoradiotherapy and surgery experienced more restenosis; hence, such patients should be carefully followed up after EBD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The included studies are summarized in Table . All studies were retrospective, and most reported outcomes of standard anterograde dilations using bougie or balloon dilators with or without guidewires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies are summarized in Table . All studies were retrospective, and most reported outcomes of standard anterograde dilations using bougie or balloon dilators with or without guidewires.…”
Section: Resultsmentioning
confidence: 99%
“…The average patient age was 60 (range 21–89) years, and there was a near 3:1 male predominance (232:87, 73%:27%) . Cancer staging and treatment data were reported variably (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BD is a common procedure used to treat CPD and pharyngo-upper esophageal strictures in dysphagia patients [2,6,10,14,15]. There have not been any studies investigated the effectiveness of BD in dysphagia management from the perspective of swallow physiology changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been used to treat Cricopharyngeal Muscle Achalasia (CMA), such as rigid dilators [12] or Botox injection planning [13], but as one of more convenient, less invasive methods, Balloon Dilatation (BD) has been used in more studies to treat cricopharyngeal dysfunction and pharyngo-upper esophageal strictures [2,6,10,[14][15][16]. It has been shown to improve UES relaxation and pharyngeal contraction amplitudes [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation